Asparagine and dough quality: Gluten strength relationships in hard red spring wheat. Issue 1 (21st December 2022) - Trevisan, Susane; Salimi Khorshidi, Ali; Sopiwnyk, Elaine; Xie, Yi; Zhou, Zhaoxian; House, James D.; Scanlon, Martin G.
Abstract: Background and objectives: The presence of acrylamide, a probable carcinogen, is a global concern for the baking industry. The reduction of free asparagine in wheat is an effective strategy to mitigate acrylamide formation. However, field‐based strategies for this purpose also affect gluten strength and bread quality. Therefore, we investigated the relationship between wheat free asparagine concentration, gluten strength and whole wheat bread quality for an extensive set of hard red spring wheat samples. Findings: Gluten strength parameters negatively correlated to wheat free asparagine concentration and showed strong inverse correlations to wheat free asparagine concentration per unit mass of protein. Reducing free asparagine concentration in the wheat did not affect the quality of the bread. Conclusions: In efforts to deliver wheat grains with a low acrylamide‐formation potential, wheat producers can apply strategies, for example, variety selection, that will reduce free asparagine without worries that gluten strength and bread quality will be impaired. Significance and novelty: Safety concerns regarding free asparagine in wheat have elicited much attention from cereal scientists and the breadmaking industry. However, the effects of reducing free asparagine on gluten strength have not been systematically studied in the literature. This comprehensive study shows that there is an inverse relationship between gluten strength and wheat free asparagine concentration.